Lyapunov Optimization-Based Online Positioning in UAV-Assisted Emergency Communications - Kang, Junghwa; Kim, Kyeongrok; Lee, Howon; Kim, Jae Hyun (IEEE Access, 2023)
In disasters, unmanned aerial vehicles (UAVs) can be used as aerial base stations (BSs) when terrestrial BSs are unavailable. Although most studies have focused on optimal UAV localization to provide efficient network connectivity for outdoor users, supporting indoor users is also of great importance. Additionally, fairly providing network connectivity to as many indoor users as possible is critical in emergencies. Therefore, we propose a table-based fair transmission algorithm based on carrier-sense multiple access with collision avoidance (CSMA/CA) that aims to provide as many equal opportunities as possible. Moreover, we propose a Lyapunov optimization-based optimal UAV positioning algorithm to satisfy various disaster requirements. To analyze the proposed algorithm's performance, two building types were considered: standard- and factory-type buildings. We then compared the proposed table-based fair transmission algorithm with the conventional protocol according to various building types. Furthermore, via intensive simulations, we demonstrated the Lyapunov optimization-derived UAV movements according to situational requirement variations.
Keywords: Aerial vehicle; Emergency communication; Indoor-to-outdoor; Indoor-to-outdoor path loss model; Lyapunov optimization; Online unmanned aerial vehicle positioning; Optimisations; Path loss models; Propagation loss; Unmanned aerial vehicle; Unmanned aerial vehicle-assisted emergency communication; Vehicle positioning; indoor-to-outdoor path loss model; Lyapunov optimization; online UAV positioning; UAV-assisted emergency communications; Unmanned aerial vehicle